Students’ Perceptions on Ice Breaking Activities related to Speaking Skill: Toilet Paper Game and Attendance Checking Questions - Mentari Putrirahayu Prawira; M. Handi Gunawan; Irma D. Lenggani (Universitas Sarjanawiyata Tamansiswa, 2025)
The COVID-19 pandemic in 2019 compelled students to stay at home and engage in remote learning for nearly two years, giving rise to the so-called “COVID generation”—students who often face difficulties in classroom communication and anxiety when addressed by teachers. This study aims to perform a qualitative analysis of junior high school students’ perceptions of ice-breaking activities related to speaking skills, specifically the